COMMENT
Two state kinetic scheme synapse described by rise time tau1,
and decay time constant tau2. The normalized peak condunductance is 1.
Decay time MUST be greater than rise time.
The solution of A->G->bath with rate constants 1/tau1 and 1/tau2 is
A = a*exp(-t/tau1) and
G = a*tau2/(tau2-tau1)*(-exp(-t/tau1) + exp(-t/tau2))
where tau1 < tau2
If tau2-tau1 -> 0 then we have a alphasynapse.
and if tau1 -> 0 then we have just single exponential decay.
The factor is evaluated in the
initial block such that an event of weight 1 generates a
peak conductance of 1.
Because the solution is a sum of exponentials, the
coupled equations can be solved as a pair of independent equations
by the more efficient cnexp method.
ENDCOMMENT
NEURON {
POINT_PROCESS ExpGABAab
RANGE tau1a, tau2a, tau1b, tau2b, ea, eb, i, sid, cid
NONSPECIFIC_CURRENT i
RANGE ga, gb
GLOBAL totala, totalb
}
UNITS {
(nA) = (nanoamp)
(mV) = (millivolt)
(uS) = (microsiemens)
}
PARAMETER {
tau1a=.1 (ms) <1e-9,1e9>
tau2a = 10 (ms) <1e-9,1e9>
ea=0 (mV)
tau1b=.1 (ms) <1e-9,1e9>
tau2b = 10 (ms) <1e-9,1e9>
eb=0 (mV)
sid = -1 (1) : synapse id, from cell template
cid = -1 (1) : id of cell to which this synapse is attached
}
ASSIGNED {
v (mV)
i (nA)
ga (uS)
factora
totala (uS)
gb (uS)
factorb
totalb (uS)
}
STATE {
Aa (uS)
Ba (uS)
Ab (uS)
Bb (uS)
}
INITIAL {
LOCAL tpa, tpb
totala = 0
totalb = 0
if (tau1a/tau2a > .9999) {
tau1a = .9999*tau2a
}
if (tau1b/tau2b > .9999) {
tau1b = .9999*tau2b
}
Aa = 0
Ba = 0
Ab = 0
Bb = 0
tpa = (tau1a*tau2a)/(tau2a - tau1a) * log(tau2a/tau1a)
factora = -exp(-tpa/tau1a) + exp(-tpa/tau2a)
factora = 1/factora
tpb = (tau1b*tau2b)/(tau2b - tau1b) * log(tau2b/tau1b)
factorb = -exp(-tpb/tau1b) + exp(-tpb/tau2b)
factorb = 1/factorb
}
BREAKPOINT {
SOLVE state METHOD cnexp
ga = Ba - Aa
gb = Bb - Ab
i = ga*(v - ea) + gb*(v - eb)
}
DERIVATIVE state {
Aa' = -Aa/tau1a
Ba' = -Ba/tau2a
Ab' = -Ab/tau1b
Bb' = -Bb/tau2b
}
NET_RECEIVE(weight (uS)) {
LOCAL srcid, w
if (weight > 999) {
srcid = floor(weight/1000) - 1
w = weight - (srcid+1)*1000
}else{
w = weight
}
Aa = Aa + w*factora
Ba = Ba + w*factora
totala = totala+w
Ab = Ab + w*factorb/3.37
Bb = Bb + w*factorb/3.37
totalb = totalb+w/3.37
}